To grow old: regulatory role of ethylene and jasmonic acid in senescence - Kim, Joonyup; Chang, Caren; Tucker, Mark L. (Frontiers in Plant Science, 2015)
Senescence, the final stage in the development of an organ or whole plant, is a genetically programmed process controlled by developmental and environmental signals. Age-related signals underlie the onset of senescence in specific organs (leaf, flower, and fruit) as well as the whole plant (monocarpic senescence). Rudimentary to most senescence processes is the plant hormone ethylene, a small gaseous molecule critical to diverse processes throughout the life of the plant. The role of ethylene in senescence was discovered almost 100 years ago, but the molecular mechanisms by which ethylene regulates senescence have been deciphered more recently primarily through genetic and molecular studies in Arabidopsis. Jasmonic acid (JA), another plant hormone, is emerging as a key player in the control of senescence. The regulatory network of ethylene and JA involves the integration of transcription factors, microRNAs (miRNAs), and other hormones. In this review, we summarize the current understanding of ethylene’s role in senescence, and discuss the interplay of ethylene with JA in the regulation of senescence.